2005
DOI: 10.1038/sj.jhh.1001941
|View full text |Cite
|
Sign up to set email alerts
|

Effects of losartan and irbesartan on serum uric acid in hypertensive patients with hyperuricaemia in Chinese population

Abstract: Therapy with losartan compared to irbesartan was performed in a Chinese sample of hypertensive patients with elevated serum uric acid (SUA) levels. After 1 week of screening and a 2 week single-blinded placebo baseline period, patients were treated for 4 weeks with losartan 50 mg or irbesartan 150 mg. After 4 weeks, patients with SiDBPo90 mmHg and SiSBPo140 mmHg continued the same dose regimen for another 4 weeks. If blood pressure was not controlled after 4 weeks of treatment, the dose of either regimen was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 13 publications
1
30
1
1
Order By: Relevance
“…Thiazide diuretics reportedly increase whereas losartan and ACEi lower uric acid levels (41)(42)(43). In our study, uric acid levels were significantly higher among patients who reported use of thiazide diuretics but use did not confound the relationship between uric acid and cC-GFR.…”
Section: Discussionsupporting
confidence: 44%
“…Thiazide diuretics reportedly increase whereas losartan and ACEi lower uric acid levels (41)(42)(43). In our study, uric acid levels were significantly higher among patients who reported use of thiazide diuretics but use did not confound the relationship between uric acid and cC-GFR.…”
Section: Discussionsupporting
confidence: 44%
“…In this analysis, long-lived subjects with cancer, secondary hypertension, severe heart failure, terminal stage of chronic obstructive pulmonary disease, Alzheimer's disease and Parkinson's disease were excluded. We also excluded subjects who self-reported use of drugs affecting uric acid, such as allopurinol or uricosuric agents, losartan, which have been shown in humans to decrease serum uric acid, 21,22 and diuretic, which could increase serum uric acid concentration. The study population ultimately consisted of 832 long-lived subjects.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The inhibition of URAT1 by irbesartan exceeded those of losartan in vitro. A large clinical study indicated that the uric acid-lowering effect of irbesartan was less than that of losartan in hypertensive patients with hyperuricemia 22) . These previous studies indicated that the effect of irbesartan on uric acid metabolism in hypertensive patients is still unclear.…”
Section: Discussionmentioning
confidence: 99%